The learning of german as a foreign language: UMCE Students, first term 2013 (Contextos: Estudios de Humanidades y Ciencias Sociales, 2017)
This article is the result of a research conducted during the first half of 2013. The question was to know under what conditions our students enter the university in relation to their com- munication skills in foreign languages. This motivated developing, in the first place, six sur- veys, in order to obtain the students’ perception regarding those skills developed during their school period, i.e. listening comprehension, reading comprehension, oral communication and written communication. First, the results are presented in terms of percentage regarding the students’ perception of their level of development of the skills mentioned above. Then, each of the skills and their content are mentioned and also quantified in percentages. Finally, the less developed skills and activities are summarized, those having exclusively less than 50% of perception development.